Navigating Legal Constraints in Asnaf Housing Development on Waqf Land in Malaysia - Asiah Aqilah Abdul Ghani; Md Yazid Ahmad; Nurul Ilyana Muhd Adnan; Mohd Nasran Mohamad; Mustapha Sheikh; Salameh Mohammad Rida Al-Omari (PT. Islamic Research Publiser, 2026)
Zakat and waqf are Islamic social finance instruments with considerable potential to address the housing needs of the asnaf in Malaysia through a combination of immediate financial support and long-term asset-based provision. However, sustainable asnaf housing remains difficult to realise despite the increasing number of housing initiatives undertaken by zakat and waqf institutions under the State Islamic Religious Councils. This difficulty is not attributable solely to financial and administrative constraints, but also reflects structural legal and institutional issues, including regulatory fragmentation, the legal status of waqf land, institutional disharmony among State Islamic Religious Councils, and the absence of clear legal engineering mechanisms for integrating zakat and waqf in housing development. Existing studies have largely examined zakat and waqf separately, leaving a significant gap in the absence of an operational legal and institutional framework for their integration into asnaf housing development in Malaysia. Accordingly, this study aims to examine the theoretical foundations of zakat waqf integration and to analyse the principal challenges affecting asnaf housing and waqf land development. The study employed a qualitative narrative literature review supported by thematic content analysis of primary and secondary sources, including academic journals, research reports, books, and relevant legal materials. The findings show that asnaf housing problems are shaped by interrelated economic, governance, and legal factors, including limited access to adequate housing, financing constraints, weak waqf asset management, fragmented institutional practices, and unresolved legal issues that hinder the operational integration of zakat and waqf. This study contributes by demonstrating that the challenge of asnaf housing development is not merely a matter of welfare delivery or resource limitation. However, it reflects a structural gap in the legal and institutional construction of zakat and waqf governance within Malaysia’s multi-layered legal system.